Sensor-based precision nutrient and irrigation management enhances the physiological performance, water productivity, and yield of soybean under system of crop intensification - Sachin, K. S.; Dass, Anchal; Dhar, Shiva; Rajanna, G. A.; Singh, Teekam; Sudhishri, Susama; Sannagoudar, Manjanagouda S.; Choudhary, Anil K.; Kushwaha, Hari Lal; Praveen, B. R.; Prasad, Shiv; Sharma, Vinod Kumar; et al. (Frontiers in Plant Science, 2023)
A two-year field study was undertaken with precision nutrient and irrigation management under system of crop intensification (SCI) on soybean crop. The experiment consisted of three irrigation regimes [I1:Standard flood irrigation at 50% depletion of available soil moisture (DASM) (FI), I2 : Sprinkler irrigation at 80% ETC (crop evapo-transpiration) (Spr 80% ETC), and I3: Sprinkler irrigation at 60% ETC (Spr 60% ETC)] assigned in main-plots, with five precision nutrient management (PNM) practices{PNM1-[SCI protocol], PNM2-[RDF, recommended dose of fertilizer : Basal dose incorporated (50% N, full dose of P & K)], PNM3-[RDF: Basal dose point placement (BDP) (50% N, full dose of P & K)], PNM4-[75% RDF: BDP (50% N, full dose of P & K)] and PNM5-[50% RDF: BDP (50% N, full P & K)]}. The adoption of Spr 80% ETC resulted in an increment of 25.6 %, 17.6 %, 35.4% and 17.5 % in net-photosynthetic rate (Pn), transpiration rate (Tr), stomatal conductance (Gs), and intercellular CO2 concentration (Ci), respectively over FI. Among PNM plots, adoption of PNM3 resulted a significant improvement in photosynthetic characters. Likewise, canopy temperature depression (CTD) in soybean reduced by 3.09-4.66 0 C due to adoption of sprinkler irrigation. Futhermore, Spr 80 % ETc recorded highest irrigation water productivity (1.08kg ha -1 m -3 ) and economic water productivity (27.5 INR ha -1 m -3 ) over conventional cultivation. Multiple correlation and PCA showed a positive correlation between physiological, growth and yield parameters of soybean. Concurrently, adoption of Spr 80% ETC with PNM3 recorded significantly higher grain yield (2.63 t ha -1 ) and biological yield (8.37 t ha -1 ) over other combinations. Thus, the performance of SCI protocols under sprinkler irrigation was found to be superior over conventional practices.